The role of intellectual property rights in seed technology transfer through trade: evidence from U.S. field crop seed exports. (5th June 2018) - Zhou, Minyu; Sheldon, Ian; Eum, Jihyun
Abstract: A panel of 134 countries over the period 1985–2010 is used to evaluate the effect of intellectual property rights (IPRs) on field crop seed imports from the United States. Based on estimating a gravity equation using the Heckman selection and Poisson fixed‐effects panel econometric methods, the results indicate that membership of countries in both the International Union for the Protection of New Varieties of Plants and the Trade‐Related Aspects of Intellectual Property Rights Agreement of the World Trade Organization have a positive and statistically significant effect on their imports of U.S. field crop seeds. These results, however, are also sensitive to both income level of importing countries and better enforcement of IPRs by those countries.